Computational optimization and investigation of conjugate heat and mass transfer in porous cavity / Azeem - Azeem, - (2017)
Conjugate heat transfer in porous medium is a complex phenomenon that depends on coupled partial differential equations which are difficult to solve directly. The governing equations of conjugate heat transfer are coupled to each other thus any change in one equation affects the other equations and vice-versa. The governing equations are nondimensionalised with the help of suitable non-dimensional parameters. These equations can be solved with the help of few numerical methods but that involves generation of huge number of simpler equations. The large number of equation evolved takes enormous amount of computational resources to solve and study the phenomenon. The current research is undertaken to develop an optimized algorithm that takes lesser amount of time to solve the resulting equations from application of a popular numerical techniques known as finite element method. The governing partial differential equations are converted into a set of algebraic equations that further assembled into a matrix form of equations. The porous solid domain subjected to conjugate heat transfer is divided into smaller segments with the help of triangular elements. The stiffness matrix of each element is assembled into a global stiffness matrix. A tight convergence criterion is maintained for all the governing equations. The optimized algorithm is compared with its conventional method of solution for conjugate heat transfer as well as conjugate heat and mass transfer. It is found that the developed algorithm works perfectly to predict the single diffusion as well as double diffusion in a square porous cavity having a small solid placed at various locations. The developed algorithm is found to take considerable lesser amount of iterations and time to arrive at the solution as compared to its counterpart i.e. conventional method of solution for conjugate heat transfer. The study revealed that the placement of solid has significant effect on the heat and mass transfer behavior in the cavity.